2017
DOI: 10.1007/s10973-017-6139-1
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic F127 as a suitable carrier for preparing the imatinib base solid dispersions and its potential in development of a modified release dosage forms

Abstract: In recent years, considerable attention focuses on making sustained release dosage forms also containing solid dispersions. The objective of this study is evaluation of imatinib base (IMA) solid dispersion physicochemical properties which can be useful to controlled release solid dosage formation. The solid dispersions were obtained by kneading method, containing of 10-90% w/w Pluronic F127 (PLU). Drug dissolution test was determined by rotating-disc system method in 0.1 M hydrochloric acid (pH 1.2) and phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 11 publications
4
22
0
1
Order By: Relevance
“…In this study, PL works by forming eutectic mixture with APG in all SDs as indicated by DSC thermograms of different SDs. DSC thermograms of SDs prepared by kneaded, melted and microwave technology showed two peaks (one at around 50 0 C) and second at around 345 0 C, suggesting formation of eutectic mixture between PL and APG in all SDs (Karolewicz et al, 2017). The melting temperature of APG was recorded as 366.36 ° C by Huang et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, PL works by forming eutectic mixture with APG in all SDs as indicated by DSC thermograms of different SDs. DSC thermograms of SDs prepared by kneaded, melted and microwave technology showed two peaks (one at around 50 0 C) and second at around 345 0 C, suggesting formation of eutectic mixture between PL and APG in all SDs (Karolewicz et al, 2017). The melting temperature of APG was recorded as 366.36 ° C by Huang et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…Pure CLT showed a distinct N=N stretching peak of tetrazole at 1666 cm −1 and a C=C stretching band at 1504 cm −1 [ 35 ]. POX exhibited a characteristic peak at 1103 cm −1 , ascribed to the stretching vibration of C-O-C [ 36 ]. Meanwhile, SLS exhibited a characteristic peak of –OSO 3 - stretching at 1229 cm −1 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…), and insoluble in THF, ethyl ether, and chloroform. The FT-IR spectrum of Plx-g-CMP (Figure 3c) shows both the specific absorption bands of CMP and Plx (2890 cm −1 (C-H stretching aliphatic), 1385 cm −1 (in-plane O-H bend) and 1112 cm −1 (C-O-stretch) [58]) (see Figure 3d). In addition, a shift of the ester absorption band from 1735 to 1739 cm −1 is observed, as well as the appearance of absorption bands specific to the amide bond (1635 cm −1 (C=O, amide I), 1554 cm −1 (coupling NH and CN, amide II) and 1450 cm −1 (C-N stretch, amide III)), which demonstrates the coupling of poloxamer to the carboxymethyl pullulan chain through an amide bond.…”
Section: Ds (%) =mentioning
confidence: 99%